THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN CREATING CHATBOTS IN THE UZBEK LANGUAGE - Mukhtashamova Parvina Zakhitovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper investigates the function of artificial intelligence (AI) in creating Uzbek-language chatbots. It highlights the significance of natural language processing (NLP), the difficulties associated with languages that have limited resources, and the real-world uses of chatbots across various industries. Additionally, the research proposes future avenues for enhancing AI systems for the Uzbek language.